(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Molecular hydrogen (H₂) is considered a fuel of the future, as carbon-based energy reserves are gradually being depleted and are non-renewable. Research has shown that representatives of the Clostridium genus produce molecular H₂ through dark fermentation by utilizing various carbon sources. Coffee silverskin (CS) produced as a result of coffee roasting process represents low-cost substrate for H₂ production. In this study H₂ production was investigated using Clostridium beijerinckii DSM791 and Clostridium pasteurianum DSM525 strains, with crude CS as the carbon source with final concentrations of 20-80 g L-1, as well as a combination of waste-with glucose (8 g L-1). Glucose was used as the sole carbon source in the positive control. H₂ production was observed in all samples starting from the 24th hour. It was shown that the maximum H₂ production occurred when the waste-glucose combination was used as the carbon source. In the control samples, the maximum H₂ production was observed at the 72nd hour, with C. pasteurianum producing 30 mM, and C. beijerinckii producing 22 mM. In the waste-glucose combination, the maximum H₂ production was observed at the 48th hour in the 60 g L-1 sample of C. pasteurianum, which exceeded the control by 2.5 fold. In C. beijerinckii, the maximum production was observed at the 72nd hour in the 40 g L-1sample, which exceeded the control by approximately 1.2 times. When only waste was used as the carbon source, the maximum production was observed at the 72nd hour in the 80 g L-1 CS containing sample of C. pasteurianum, with 18 mM, and in the 60 g L-1 sample of C.beijerinckii, with 7 mM. Thus, it can be concluded that untreated CS can be used as a carbon source for bacterial hydrogen production, although optimal concentrations should be chosen to maximize industrial hydrogen yields.